Penyusunan Laporan Keuangan Menggunakan Aplikasi Excel Bagi GKII Daerah Tarakan, Tana Tidung, dan Nunukan - Ferica C Putri; Yohanna Thresia Nainggolan; Sulistya Rini Pratiwi (CV. Multi Kreasi Media, 2022)
Since it was definitively designated as the church's administrative area for Tarakan, Tana Tidung and Nunukan (TATATINUN) in 2021, the TATATINUN Regional GKII requires financial reports that can describe the achievement of regional performance for the fiscal year 2021/2022. Financial reporting can be carried out by means of planning, recording and supervising church organizations. This community service activity aims to help GKII Daerah TATATINUN in preparing regional financial reports using the excel application. The community service method is carried out by means of documentation and interviews. The financial statements have been reported at the Rapat Kerja Daerah I and are used as the basis for preparing the financial system work program that will be implemented for the fiscal year 2022/2023.